Analysis of Non-Cash Transactions, Debit Cards, Credit Cards, and Electronic Money, on the Money Supply in Indonesia - Astuty, Sri (PT. Maju Malaqbi Makkarana, 2023)
This study was conducted to determine the effect between the independent variable, namely non-cash transactions (debit card transactions, credit card transactions, and electronic money transactions) on the dependent variable, namely the Money Supply (M1) in Indonesia. The research was conducted using a quantitative approach and the type of research used secondary data in the form of time series data from 2012-2021 obtained from Bank Indonesia and the Central Bureau of Statistics. The purpose of this study is to determine the effect of non-cash transactions on the money supply in Indonesia during 2012-2021. The analysis model used is multiple linear regression using SPSS. This study also uses the statistical t test, statistical F test, and the coefficient of determination R2. Based on the results of the research that has been done, it shows that debit card transactions have a positive effect on the amount of money in circulation and credit card transactions have a negative effect on the money supply in 2012-2021. Meanwhile, electronic money transactions have no effect on the money supply in 2012-2021